Pengaruh Kepemimpinan Transaksional, Kepemimpinan yang Melayani, dan Integritas Kerja terhadap Kinerja Karyawan - Agustin Kristian Puji Lestari; Nur Hidayati; Zaenul Muttaqien (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the influence of transactional leadership, servant leadership, and work integrity on employee performance at PT. Istana Argo Kartika (Sanken) Surabaya Branch. The research applies a quantitative approach with an associative design to examine the relationships among variables. The population consists of all permanent employees, and because the total number is limited, a saturated sampling technique was used so that every employee could serve as a respondent. Data were collected through structured questionnaires and later analyzed using multiple linear regression to determine both partial and simultaneous effects. The findings reveal that transactional leadership, servant leadership, and work integrity each have a positive and significant impact on employee performance when tested individually. In addition, the combined influence of all three variables also shows a significant contribution to overall performance levels. These results suggest that firm direction, supportive service-oriented leadership, and strong adherence to integrity can effectively improve employee outcomes. Therefore, this study is expected to provide useful insights for management in designing leadership development programs and strengthening human resource strategies.